The context of nursing care for women with breast cancer: literature review (Research, Society and Development, 2020)
This study aimed to understand the role of nursing care for patients affected by breast cancer and undergoing mastectomy. This is a bibliographic review work that allowed the gathering of studies that discuss the theme. The research found the role of the nurse in the face of the breast diagnosis, still considered an introvert due to the scarcity of public policies guiding the action of the nursing professional. Much of the work is still repressed in primary health care. And, that, the technical skills are not the only ones necessary to provide qualified care to mastectomized patients, as humanized actions become relevant for both the patient and the family. Thus, it is concluded that the nurse must be prepared to provide quality care. Further studies on the subject are needed to support the identification, description of the role and advocacy of policies and programs that can better detail and specify nursing care in the early diagnosis of breast cancer and post mastectomy.